Study of the urbanization of the districts of Chorrillos, Miraflores, and Barranco according to the story «Los pacayares» by Ricardo Palma - Belladoni Portal, Oriana Francesca (2022)
This article is based on the story «Los pacayares», by Ricardo Palma, which describes the plots of land known as pacayares, which, over the years, became quintas or country houses, and then modern houses that are part of the urbanizations. For our study, we will consider the districts of Chorrillos, Miraflores, and Barranco. We are interested in addressing the evolution and use of spaces from the mid-19th century to the contemporary period; above all, we want to emphasize the process of formal and informal urbanization and an appreciation of the variation of structural elements. An evaluation of the harmony between the areas destined for human development and the green areas will also be carried out.